Care Seeking Patterns of STIs-Associated Symptoms in Iran: Findings of a Population-Based Survey - Maryam Nasirian; Mohammad Karamouzian; Kianoush Kamali; Amir Reza Nabipour; Ahmad Maghsoodi; Roja Nikaeen; Ali Reza Razzaghi; Ali Mirzazadeh; Mohammad Reza Baneshi; Ali Akbar Haghdoost (Kerman University of Medical Sciences, 2016)
Background Understanding the prevalence of symptoms associated with sexually transmitted infections (STIs) and how care is sought for those symptoms are important components of STIs control and prevention. People's preference between public and private service providers is another important part of developing a well-functioning STIs surveillance system. Methods This cross-sectional survey was carried out in spring 2011, using a nonrandom quota sample of 1190 participants (52% female) in 4 densely-populated cities of Tehran, Kerman, Shiraz, and Babol. Two predictive logistic regression models were constructed to assess the association between the socio-demographic determinants (independent variables) and the dependent variables of history of STIs-associated symptom and seeking care. Results Around 57% (677 out of 1190; men: 29.70% and women: 81.80%) had experienced at least one STIsassociated symptom during the previous year. History of experiencing STIs-associated symptoms among men, was negatively significantly associated with older age (adjusted odds ratio [AOR] = 0.34, CI 95%: 0.17-0.67). Women who were married, in older ages, and had higher educations were more likely to report a recent (past year) STIs symptom, however all were statistically insignificant in both bivariate and multivariable models. Among those who have had STIs-associated symptoms in the last year, 31.15% did nothing to improve their symptoms, 8.03% attempted self-treatment by over-the-counter (OTC) medications or traditional remedies, and 60.93% sought care in health facilities. In both bivariate and multivariable analyses, care seeking among men was insignificantly associated with any of the collected demographic variables. Care seeking among women was positively significantly associated with being married (AOR = 2.48, 95% CI: 1.60-3.84). Conclusion The reported prevalence of STIs-associated symptoms among our participants is concerning. A considerable number of participants had delayed seeking care and treatment or self-medicated. People should be informed about their sexual health and the consequences of delaying or avoiding seeking care for STIs. Participants preferred seeking care at private sectors which calls for engaging both public and private health sectors for reporting and following up STIs cases.